2013
DOI: 10.1007/s13762-013-0185-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the organophosphate pesticide diazinon to crayfish of differing age

Abstract: Diazinon is a widely applied agricultural pesticide whose effect importantly on the environment and the possible contamination of surface waters has led to increased interest in toxicological studies. Crayfish, as an ecologically important benthic macroinvertebrate, seems to be an appropriate model organism for such assessments. Acute toxicity tests were carried out on three crayfish age groups: young-of-the-year (total length = 25.0 ± 4.9 mm), juvenile (total length = 56.5 ± 3.8 mm) and adult (total length = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The remaining four taxa in the nine candidate bioindicators are all green algae in the family Scenedesmaceae. Congeners of these taxa have been previously found to co‐occur with crayfish, and have been shown to be sensitive to crayfish pesticides (Buřič et al, 2013; Sarιkaya et al, 2011), suggesting that they may constitute important habitat for P. clarkii . We note that invasive tilapia were also present in our study system, potentially inflating the number of taxa significantly associated with crayfish in the pre‐eradication samples.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining four taxa in the nine candidate bioindicators are all green algae in the family Scenedesmaceae. Congeners of these taxa have been previously found to co‐occur with crayfish, and have been shown to be sensitive to crayfish pesticides (Buřič et al, 2013; Sarιkaya et al, 2011), suggesting that they may constitute important habitat for P. clarkii . We note that invasive tilapia were also present in our study system, potentially inflating the number of taxa significantly associated with crayfish in the pre‐eradication samples.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining four taxa in the 9 candidate bioindicators are all green algae in the family Scenedesmaceae. Congeners of these taxa have been previously found to co-occur with crayfish, and have been shown to be sensitive to crayfish pesticides (Buřič et al, 2013; Sarıkaya et al, 2011), suggesting that they may constitute important habitat for P. clarkii . We note that invasive tilapia were also present in our study system, potentially inflating the number of taxa significantly associated with crayfish in the pre-eradication samples.…”
Section: Discussionmentioning
confidence: 99%
“…Congeners of these taxa have been previously found to co-occur with crayfish, and have been shown to be sensitive to crayfish pesticides (Buřič et al, 2013;Sarιkaya et al, 2011), suggesting that they may constitute important habitat for P. clarkii.…”
Section: Candidate Bioindicators Of Crayfish Presence Are Valuable To...mentioning
confidence: 99%
“…In contrast to cavefishes, we found that cave crayfishes had a strong negative relationship with human disturbance. Cave crayfishes may be more influenced than cavefishes by humaninduced landscape changes because of pesticide applications in urban and agricultural settings that specifically www.nature.com/scientificreports/ target arthropods 78,79 . Follow-up testing of the chemical constituents present in runoff may be warranted to better understand mechanisms on species persistence.…”
Section: Discussionmentioning
confidence: 99%